Solubility enhancement of milk protein isolate by sodium caseinate addition: Comparison between wet- and dry-blending approaches. (June 2020) - Bot, Francesca; Crowley, Shane V.; O'Mahony, James A.
Abstract: This study investigated the physicochemical properties of milk protein isolate (MPI) suspensions when sodium caseinate (NaCAS) was incorporated by wet- or dry-blending. The studied MPI had a solubility of only 89.6% when it was the sole contributor to total protein. In dry-blended samples, solubility was increased to a maximum of 97.5% when NaCAS contributed 15% to total protein. High volumes of micellar casein (73.2%) and low volumes of primary powder particles (27.8%) were measured in dry-blended systems with 15.0% NaCAS addition, corresponding to high suspension stability. Wet blending only improved the solubility slightly to 92.3% and resulted in a large volume of primary powder particles. Differences in physicochemical properties between dry and wet-blending might be attributed to the strong tendency of NaCAS to promote dissociation of casein micelles under dry-blending conditions. The results indicate the dry-blending approach represents an effective strategy for obtaining MPI/NaCAS suspensions with high solubility.